M3 Comparison of aortic valve area on computed tomography versus echocardiography. (7th September 2020) - Foley, R; Lyen, S; Manghat, N; Hamilton, M
Abstract : Introduction: The imaging standard in the diagnosis and grading of aortic stenosis is the echocardiogram. However, computed tomography (CT) offers a more anatomically precise measurement of the left ventricular outflow tract (LVOT) area and aortic valve (AoV) area. The purpose of this study was to compare the AoV area measured by echocardiogram and CT. Methods: Data was prospectively collected on all patients undergoing CT for consideration of transcatheter aortic valve implantation (TAVI) from July 2019 - January 2020. Measurements of LVOT and AoV area were performed using validated software (TeraRecon, California). Echocardiographic measurements of the LVOT, peak velocity across the LVOT and the AoV were used to derive the AoV area using the continuity equation. Spearman correlation analysis was performed using R v3.3.3. Results: There were 19 patients in whom contemporaneous echocardiography was available. CT derived AoV area was positively correlated with echocardiographic measurements of AoV area (rs =0.54, p= 0.02) and LVOT area (rs =0.58, p< 0.01). However, echocardiography led to an underestimation of both LVOT area and AoV area. 89% of the error in AoV area estimation at echocardiography was due to LVOT measurement error. The combination of echocardiographic measurements of velocity with CT derived LVOT area led to improved estimation of AoV area, (rs =0.75, p< 0.01). Conclusion: The use of the continuity equation on echocardiography leads to underestimation of the AoV area. The combination of echocardiography and CT measurements makes the continuity equation estimate of CT area near the same as CT planimetry.